Can one cure the nonunitarity of three-dimensional quadratic gravity using a topological Chern-Simons term? - Accioly, Antonio [UNESP] (Elsevier, 2004)
Quadratic gravity in (2+1)D is nonunitarity at the tree level. When a topological Chern-Simons term is added to this theory, the harmless massive scalar mode of the former gives rise to a troublesome massive spin-0 ghost, while the massive spin-2 ghost is replaced by two massive physical particles both of spin-2. Therefore, unlike what it is claimed in the literature, quadratic Chern-Simons gravity in (2+1)D is nonunitary at the tree level. © 2004 Published by Elsevier B.V.